Cutaneous leukocyte lineages in tolerant large animal and immunosuppressed clinical vascularized composite allograft recipients. Issue 2 (29th August 2020) - Leonard, David A.; Powell, Harrison R.; Defazio, Matthew W.; Shanmugarajah, Kumaran; Mastroianni, Melissa; Rosales, Ivy A.; Farkash, Evan A.; Colvin, Robert B.; Randolph, Mark A.; Sachs, David H.; Kurtz, Josef M.; Cetrulo, Curtis L.
Abstract : Vascularized composite allografts (VCAs) can restore fully functional anatomic units in patients with limb amputations or severe facial tissue loss. However, acute rejection of the skin is frequently observed and underscores the importance of developing tolerance induction protocols. In this study, we have characterized the skin immune system in VCAs. We demonstrate infiltration of recipient leukocytes, regardless of rejection status, and in tolerant mixed hematopoietic chimeras, the co‐existence of these cells with donor leukocytes in the absence of rejection. Here we characterize the dermal T cell and epidermal Langerhans cell components of the skin immune system in our porcine model of VCA tolerance, and the kinetics of cutaneous chimerism in both of these populations in VCAs transplanted to tolerant and nontolerant recipients, as well as in host skin. Furthermore, in biopsies from the first patient to receive a hand transplant in our program, we demonstrate the presence of recipient T cells in the skin of the transplanted limb in the absence of clinical or histological evidence of rejection. Abstract : The authors show that recipient leukocytes infiltrate the skin of vascularized composite allografts and, in tolerant large animal recipients and in an immunosuppressed hand recipient, coexist with donor leukocytes without evidence of rejection.